Elaboración de bloques nutricionales a base de subproductos de mercado (lechuga, col y cáscara de papa) para la alimentación de cuyes machos (Cavia porcellus) durante las 6 primeras semanas postdestete - Quingaluisa Cuji, Marcia del Rocio (2021)
Small and medium producers of guinea pigs administer green forage to their animals as the only diet, so they do not satisfy the nutritional needs of guinea pigs to fulfill their productive stage. For this reason, it is proposed to include nutritional blocks based on market by-products (lettuce, cabbage, and potato peel) in the feeding of male guinea pigs (Cavia porcellus) during the first six weeks after weaning and thus satisfy the nutritional needs of the guinea pigs. For which 36 Creole male guinea pigs of one month were used with an average weight of 483.27g distributed under a completely random design with three repetitions and four treatments constituted as follows, T0 (alfalfa), T1 (alfalfa + lettuce), T2 (alfalfa + cabbage) and T4 (alfalfa + potato peel). When evaluating the productive variables, there were no statistical differences (P> 0.05) between the means of the treatments according to Duncan's Test. However, there is a numerical difference where it was observed that T3 (potato peel) obtained the highest final weight with 888.78g and a weight gain of 59.67g, the treatments that consumed the most food were T1 (lettuce) with a value of 246.62g, T2 (cabbage) and T3 (potato peel) with 245.72g. Regarding the efficiency in food conversion, T3 (potato peel) with a value of 4.15 obtained a better conversion. Under the results presented, the implementation of nutritional blocks to the guinea pig diet can be considered a feeding alternative when forage is scarce. Providing the necessary nutrients for the guinea pig to fulfill its formative stage and the producers obtain better profits because accessible and profitable products are used, generating a positive impact on the environment because they are waste products that can be reused